(x)(x+1)=600

Simple and best practice solution for (x)(x+1)=600 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x)(x+1)=600 equation:


Simplifying
(x)(x + 1) = 600

Reorder the terms:
x(1 + x) = 600
(1 * x + x * x) = 600
(1x + x2) = 600

Solving
1x + x2 = 600

Solving for variable 'x'.

Reorder the terms:
-600 + 1x + x2 = 600 + -600

Combine like terms: 600 + -600 = 0
-600 + 1x + x2 = 0

Factor a trinomial.
(-25 + -1x)(24 + -1x) = 0

Subproblem 1

Set the factor '(-25 + -1x)' equal to zero and attempt to solve: Simplifying -25 + -1x = 0 Solving -25 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + -1x = 0 + 25 Combine like terms: -25 + 25 = 0 0 + -1x = 0 + 25 -1x = 0 + 25 Combine like terms: 0 + 25 = 25 -1x = 25 Divide each side by '-1'. x = -25 Simplifying x = -25

Subproblem 2

Set the factor '(24 + -1x)' equal to zero and attempt to solve: Simplifying 24 + -1x = 0 Solving 24 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -1x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1x = 0 + -24 -1x = 0 + -24 Combine like terms: 0 + -24 = -24 -1x = -24 Divide each side by '-1'. x = 24 Simplifying x = 24

Solution

x = {-25, 24}

See similar equations:

| -3x+5-2x=65 | | 10(a+b+c)= | | x^2+y^2-6x+4y-78=0 | | 28a+10=-7 | | 1=3x-5x+5 | | 5x-6y+4(x-5)= | | 8t^2+28t=0 | | r^2-6r-55=0 | | 18=2x+7x-9 | | 42*3/6=x | | 2x+8-6x=-4 | | 5x+4+6x=48 | | 42*3/6 | | x*(x+1)=240 | | 13-2=5 | | (10000-x)(.2)=5000 | | 5x-5=3x-8 | | 8-b=-154 | | .2x+.3y=.5 | | 30+7y=2y-10 | | -6t^2+5t+56=0 | | 5x+37=x+5 | | Z-5=60 | | 4(2c-1)-5=6c+5 | | (3/8)*(5/6)=x | | r+p+2=3r-4-3p | | 5h+60=8h | | -3x-20=x+12 | | X+89=4+6x | | -16v=7 | | 4x+38=3x | | 141=3(x+3)+9x |

Equations solver categories